The simultaneous moult of female hornbills is not triggered by the darkness of their nest cavity. (2nd October 2018) - Stanback, Mark; Millican, David; Visser, Paul; Marker, Laurie
Abstract : A verbal model from 1937 proposed that the darkness of the nest cavity acts as a proximate trigger for the simultaneous moult observed in female hornbills. Although never tested, the plausibility of this hypothesis has allowed it to be cited frequently. We tested the role of darkness on the moult of Tockus hornbills by providing females with either opaque wooden nest boxes or translucent plastic ones. Most females underwent a simultaneous moult of their remiges and retrices following clutch completion, regardless of the amount of time they had spent in the nest. More importantly, the variation in the simultaneity of the flight feather moult was unrelated to box type. These results suggest that darkness does not act as a proximate cue for the simultaneous moult of female hornbills.